Efficacy of platelet-rich fibrin in papilla reconstruction: A systematic review and meta-analysis - Zohreh Afshari; Yeganeh Khazaei; Mahsa Ahmadishadmehri (Wolters Kluwer Medknow Publications, 2024)
This systematic review and meta-analysis aimed to compare the efficacy of using platelet-rich fibrin (PRF) or connective tissue graft (CTG) for papilla reconstruction in the treatment of black triangles. A comprehensive electronic search across PubMed, Cochrane, Web of Science, ProQuest, and Scopus was conducted to identify the relevant randomized-controlled trials (RCTs), cohort studies, and case series. Quality assessment and meta-analysis were performed using R Statistical Software, focusing on the parameters such as papilla height, gingival index, plaque index (PI), clinical attachment level (CAL), and pocket probing depth. Registration number: CRD42022322934. From 191 initial studies, 7 were eligible for full-text review, with 4 RCTs and one retrospective study included in the meta-analysis. The analysis favored CTG over PRF in terms of black triangle height at 3-6 months postsurgery and in PI improvement at 3 months. No significant differences were found in CAL and probing pocket depth. While PRF can yield satisfactory results in papilla augmentation, CTG demonstrates superior clinical outcomes in specific parameters. Further research with more extensive clinical data is warranted.